Implementasi Program Bursa Kerja Khusus (BKK) Dalam Perencanaan Karir Siswa Kelas XII di SMK PGRI 2 Ponorogo - Nur Asiyah; Panggih Wahyu Nugroho (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Good human resources are the main key to building a nation. The task of educational institutions is to obtain good or superior resources. SMK is education at the secondary level that prioritizes the develipment of students’ abilities to do certain jobs. Vocational higt school is one of the institutions that is requiried to produce educated skilled workers or graduates as expected by the business world and the industrial world. Ideally, SMK graduates can beabsorbed directly by the world of work, the number of SMKs which increases every year has not been able to reduce the unemployment rate as expected. This research is to analyze (1) the process of implementing the spesial job exchange program in the career planning of class XII studens (2) the service from of the spesial job exchange program in the career planning of class XII studens (3) evaluation of the service of the spesial job exchange program in the career planning of class XII studens.